2012
DOI: 10.1103/physrevlett.108.107204
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Engineering of Molecular Qubits

Abstract: We show that the electron spin phase memory time, the most important property of a molecular nanomagnet from the perspective of quantum information processing, can be improved dramatically by chemically engineering the molecular structure to optimize the environment of the spin. We vary systematically each structural component of the class of antiferromagnetic Cr(7)Ni rings to identify the sources of decoherence. The optimal structure exhibits a phase memory time exceeding 15  μs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
252
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(269 citation statements)
references
References 30 publications
12
252
1
1
Order By: Relevance
“…The original procedure for preparation of compound 16.57 mmol) resulted in a green microcrystalline product. After this, the flask was cooled to room temperature, and acetonitrile (20ml ) was added to complete the precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original procedure for preparation of compound 16.57 mmol) resulted in a green microcrystalline product. After this, the flask was cooled to room temperature, and acetonitrile (20ml ) was added to complete the precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Shells of organic ligands provide magnetic separation between adjacent magnetic cores, which behave as identical and independent zero-dimensional units [1]. The magnetic dynamics are characterized by strong quantum fluctuations and this makes MNMs of great interest in quantum magnetism as model systems to investigate a range of phenomena, such as quantum-tunnelling of the magnetization [2][3][4], Néel-vector tunnelling (NVT) [5,6], quantum information processing [7][8][9], quantum entanglement [10][11][12][13] or decoherence [14][15][16]. Besides their fundamental interest, MNMs are also the focus of intense research for the potential technological applications as classical or quantum bits [1,[7][8][9]17] and as magnetocaloric refrigerants [18].…”
mentioning
confidence: 99%
“…The same attention should be taken to reduce (electrical) noise produced by local vibrations. From this point view, the seminal work reported in [20] demonstrated that molecular engineering can be a powerful tool to control the closest environment of the spin. On the other hand, if we need to expose spins to an external environment, such as a biological system or an electronic circuit, the ligand shell may, in some ways, protect or, at least, define the closest surrounding around the sensitive spin.…”
Section: Coherent Spin Dynamics Of Spin Ensemblesmentioning
confidence: 99%
“…[5][6][7] The origin of this keen interest comes from their particular magnetic characteristics (high magnetic moments and strong magnetic anisotropy) and specific luminescence. Both SMMs and luminescent materials have a plethora of potential applications, for example, high-density data storage, spintronics and quantum computing, [8][9][10][11][12][13][14][15] organic light-emitting diodes (OLEDs), [16] time-resolved fluoro-immunoassays, [17] biosensors [18,19] and time-resolved imaging. [20] In the molecular-magnetism field, the luminescence was recently exploited to provide a high level of comprehension of the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%